2019
DOI: 10.1093/jas/skz162
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of plasma and ruminal volatile fatty acids in sheep fed alfalfa pellets and genetic correlations with enteric methane emissions1

Abstract: Animal-to-animal variation in methane (CH4) emissions determined in respiration chambers has a genetic basis, but rapid phenotyping methods that can be applied on-farm are required to enable increased genetic progress by the farming industry. Fermentation of carbohydrates in the rumen results in the formation of VFA with hydrogen (H2) as a byproduct that is used for CH4 formation. Generally, fermentation pathways leading to acetate are associated with the most H2 production, less H2 formation is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Low to moderate relationships were observed between methane yield, fleece weight, body weight and body condition score at mating. It has been shown previously that low-emitting animals tend to have a greater amount of lean tissue (Elmes et al, 2014), possibly due to greater ratios of propionate and valerate to acetate and butyrate coming from the rumen (Jonker et al, 2019). Also, Bilton et al (2021) showed that low methane ewes similarly had different volatile fatty acid profiles in their rumen fluid and less short-chain fatty acids in their milk.…”
Section: Discussionmentioning
confidence: 90%
“…Low to moderate relationships were observed between methane yield, fleece weight, body weight and body condition score at mating. It has been shown previously that low-emitting animals tend to have a greater amount of lean tissue (Elmes et al, 2014), possibly due to greater ratios of propionate and valerate to acetate and butyrate coming from the rumen (Jonker et al, 2019). Also, Bilton et al (2021) showed that low methane ewes similarly had different volatile fatty acid profiles in their rumen fluid and less short-chain fatty acids in their milk.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, genetic selection for lower gas emissions may be a feasible mitigation possibility, provided that the GHG emission traits have no high undesirable genetic correlations with animal performance traits (Elmes et al, 2014; Pinares‐Patiño et al, 2011). To this end, an efficient and valid method of ranking animals for their GHG emissions is mandatory (Jonker et al, 2019). Also, breeding plans for sheep should consider the interrelationships between productivity and the environment (Jonker et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, an efficient and valid method of ranking animals for their GHG emissions is mandatory (Jonker et al, 2019). Also, breeding plans for sheep should consider the interrelationships between productivity and the environment (Jonker et al, 2019). The low standard errors and 95% CI of the mean heritability estimates for most gas emission traits could indicate the appropriate accuracy for these estimates.…”
Section: F I G U R Ementioning
confidence: 99%
“…The location of the fluid sampling might not be consistent with the stomach tubing method, and samples can contain variable quantities of saliva contamination. These factors may affect the absolute pH and concentrations of fermentation metabolites in the rumen fluid, but not of fermentation product percentages and ratios ( Larsen et al, 2020 ), and the relative values of pH and SCFA concentrations were previously found to be useful for ranking CH 4 /DMI in sheep ( Jonker et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%